Immune modulatory microRNAs involved in tumor attack and tumor immune escape - Eichmüller, Stefan B.; Osen, Wolfram; Mandelboim, Ofer; Seliger, Barbara (Journal of the National Cancer Institute, 2017)
Current therapies against cancer utilize the patient’s immune system for tumor eradication. However, tumor cells can evade immune surveillance of CD8+ T and/or natural killer (NK) cells by various strategies. These include the aberrant expression of human leukocyte antigen (HLA) class I antigens, co-inhibitory or costimulatory molecules, and components of the interferon (IFN) signal transduction pathway. In addition, alterations of the tumor microenvironment could interfere with efficient antitumor immune responses by downregulating or inhibiting the frequency and/or functional activity of immune effector cells and professional antigen-presenting cells. Recently, microRNAs (miRNAs) have been identified as major players in the post-transcriptional regulation of gene expression, thereby controlling many physiological and also pathophysiological processes including neoplastic transformation. Indeed, the cellular miRNA expression pattern is frequently altered in many tumors of distinct origin, demonstrating the tumor suppressive or oncogenic potential of miRNAs. Furthermore, there is increasing evidence that miRNAs could also influence antitumor immune responses by affecting the expression of immune modulatory molecules in tumor and immune cells. Apart from their important role in tumor immune escape and altered tumor-host interaction, immune modulatory miRNAs often exert neoplastic properties, thus representing promising targets for future combined immunotherapy approaches. This review focuses on the characterization of miRNAs involved in the regulation of immune surveillance or immune escape of tumors and their potential use as diagnostic and prognostic biomarkers or as therapeutic targets.